Low-temperature rapid fabrication of crosslinked poly(quaterphenyl piperidine) membrane for anion exchange membrane water electrolyzers - Du Ru Kang; Gi Hyo Sim; Minjoong Kim; Jae Hun Lee; Jong Hak Kim (Journal of Membrane Science Letters)
While nonsolvent-induced phase separation (NIPS) is widely recognized as an established method for creating porous polymer membranes, this study uniquely employs a nonsolvent to produce a dense, nonporous membrane instead. Specifically, the membranes were rapidly fabricated at low temperatures using dimethyl sulfoxide (DMSO), a high-boiling-point solvent, and water as the nonsolvent. We successfully prepared a series of crosslinked poly(quaterphenyl piperidine) (PQP-BM) network membranes with high crosslinking degrees (up to 47.2 %). By combining a hydrophobic extended polyaromatic backbone with a hydrophilic piperidine-based crosslinker, we achieved distinct microphase separation, which enhanced ion transport, dimensional stability, and thermal and mechanical properties compared to the linear uncrosslinked membranes. The optimized AEM exhibited exceptional mechanical strength (tensile strength >63 MPa), high ion conductivity (151.5 mS cm⁻¹ at 80 °C), and excellent alkaline durability. In single-cell water electrolyzer tests, the PQP-BM membrane demonstrated a remarkable current density of 3.99 A cm⁻² at 2.0 V in 1 M KOH at 50 °C, outperforming the commercial FAA-3–50 membrane by 126 %. This study highlights the potential of the energy-efficient NIFF process as a scalable method for producing advanced AEMs for energy conversion applications.